Paraphrase Detection using String Similarity with Synonyms - Lee, Jun Choi; Cheah, Yu-N (2015)
This paper presents an approach to enhance text similarity using synonyms for paraphrase detection. Paraphrase detection detects sentences or texts with similar meaning. Synonym of words can help in paraphrase detection. However, considering synonyms for all the text in the comparison posted extra computational task in the process. This study introduces a simpler approach in considering synonyms in text similarity. The proposed approach is able to be adopted in any term-based text similarity metrics for paraphrase detection. The proposed approach is evaluated using the Microsoft Research Paraphrase Corpus. The evaluation show better result compares to original similarity metrics and reasonable result compares to other selected paraphrase detection approaches in previous studies